Answers

2015-10-07T18:58:42+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
You didn't specify if a,b,c are all distinct. Firste note that:

a^3 + b^3 + c^3 - 3abc = (a + b + c)(a^2 + b^2 + c^2 - ab - ac - bc).

By assumption a^3+b^3+c^3=3abc so the left hand side is 0.

Therefore (a+b+c)(a^2+b^2+c^2-ab-ac-bc) = 0. So either a+b+c=0 or a^2+b^2+c^2-ab-ac-bc=0.

Now suppose a^2+b^2+c^2 - ab-ac-bc =0. You can re-write this as:

(1/2) ( (a-b)^2 + (b-c)^2 + (c-a)^2 )=0

Therefore (a-b)^2 + (b-c)^2 + (c-a)^2 =0 so a=b=c.

So either a+b+c=0 or a=b=c. (So if a,b,c are all distinct then a+b+c=0).

1 4 1
2015-10-07T19:07:42+05:30
A^3 + b^3 + c^3 - 3abc = (a+b+c) (a^2 + b^2 + c^2 - ab - bc -ca)
So if a+b+c = 0 
then a^3 + b^3 + c^3 - 3abc = 0
So a^3 + b^3 + c^3 = 3abc
Hope it helps and pls mark as the best answer. :-)
0